Determinación del índice de madurez del Amaranto (amaranthus caudatus l.) en el sector de Salache Bajo, Cantón Latacunga, Provincia Cotopaxi, 2017 - Mañay Chimborazo, Alexandra Maricela (2018)
The main objective of this research was to generate the maturity index of amaranth (Amaranthus caudatus L.). It was carried out in the Salache Bajo Sector in the Latacunga canton, Cotopaxi province, because amaranth production is totally affected. of losses in the harvest and as well as economically for the producers in which data were recorded, from the curdling of the grain to the 30 days that its physiology lasts in terms of its harvest, likewise it was intended to expose the seeds to the study of drying to the environment until reaching 12% humidity. In this way, it serves as a guide and a great contribution to agricultural knowledge for farmers in the Salache Bajo sector, since they do not know about the maturity indexes of the crop and the proper post-harvest management for its proper conservation. This research was carried out in two study phases in which they are in the field and in the Andean grain laboratory. The methodology in the field was carried out by observing and collecting amaranth panicles in which we took 5 plants for treatments and repetitions, recording data on the maturity indices of the plant, in the laboratory phase it was carried out by studying the seeds, such as the analysis of weight, percentage of humidity, grain size, pests and diseases and percentage of germination according to the factors to be evaluated, which are maturity indices (grain set at 6, 12, 18, 24 , 30 days) that the harvest lasts and the other factor that is drying (without drying and drying in the environment up to 12% humidity) .The study methodology is experimental, inductive deductive field is constituted by 36 experimental units in a design of Completely Raise Blocks (DBCA) with, 12 treatments in an A * B factorial arrangement with 3 repetitions to identify and quantify the time when the amaranth harvest should be carried out, it will also be taken into account to some variables to measure the best index and behavior after harvest. The results of the study in which it was determined that we did not acquire results according to the maturity indices that have reliable results to be able to harvest before the plant completes the phenological cycle, in which we find the highest percentage of germination is in the index from maturity to grain setting at 30 days